2018
DOI: 10.1136/bmj.k4922
|View full text |Cite
|
Sign up to set email alerts
|

Depression in older adults

Abstract: A neglected chronic disease as important as dementia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 17 publications
2
58
0
5
Order By: Relevance
“…Depressive symptoms tend to increase when people transition from middle adulthood to older age, often together with worsening physical health. [1][2][3] Depressive symptoms among the elderly are frequently comorbid with chronic diseases, disability, and dementia, which may complicate differential diagnosis and treatment options. 3,4 Despite the adverse psychosocial effects of even mild depressive symptoms in older adults, 1,2 most people suffering from depressive symptoms do not receive adequate treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depressive symptoms tend to increase when people transition from middle adulthood to older age, often together with worsening physical health. [1][2][3] Depressive symptoms among the elderly are frequently comorbid with chronic diseases, disability, and dementia, which may complicate differential diagnosis and treatment options. 3,4 Despite the adverse psychosocial effects of even mild depressive symptoms in older adults, 1,2 most people suffering from depressive symptoms do not receive adequate treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Depressive symptoms among the elderly are frequently comorbid with chronic diseases, disability, and dementia, which may complicate differential diagnosis and treatment options. 3,4 Despite the adverse psychosocial effects of even mild depressive symptoms in older adults, 1,2 most people suffering from depressive symptoms do not receive adequate treatment. 2,3,5 Several factors can contribute to why some individuals are more or less likely to be treated.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted this case-control study in the rural setting of Bangladesh to assess the association between malnutrition and depression, and associated risk factors. A study reported that elderly depressed people have a greater risk of psychological disorders, which provoke suicide and suicidal behaviors [32]. The existing health care delivery system in Bangladesh provides limited health care for the elderly population in urban communities, but it is scarce in rural settings.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organisation (WHO) estimates that more than twenty percent of adults aged sixty and over face mental health problems [1]. While depression is the most common across all age groups, depression in late life poses speci c challenges to the individual as well as to the healthcare system [2]. Symptoms of depression in old age may be different compared to younger cohorts, showing more vegetative and somatic, rather than affective symptoms; moreover, comorbidities and associated loss of physical functioning, cognitive impairment and chronic pain may overlap with depressive symptoms [3,4].…”
Section: Introductionmentioning
confidence: 99%